Biological control of Alternaria alternata-induced black-spot disease in Dioscorea opposita using endophytic Bacillus sp. E-Do8 (Research, Society and Development, 2026)
Plant endophytic bacteria play crucial roles in the prevention and control of crop diseases. Yam (Dioscorea opposita), an important tuber and root crop, is renowned for its rich vegetable and medicinal values. However, the black-spot disease is relatively prevalent during its cultivation process, and there are no reports on using endophytes to control this disease. In this study, we aimed to investigate the biological control of black spot disease caused by Alternaria alternata in Dioscorea opposita using the endophytic bacterium Bacillus sp. E-Do8. An endophytic bacterium that strongly antagonized Alternaria alternata, the pathogen causing yam black-spot disease, was isolated from Tiegun yam leaves, and it was identified as a strain of Bacillus and named E-Do8. Further investigations revealed that the E-Do8 fermentation broth could significantly inhibit the spore germination and mycelial growth of A. alternata, and the mycelia showed uneven thickness, swelling, and irregular entanglement. Moreover, the ability of A. alternata to penetrate cellophane was weakened when cultured with the E-Do8 fermentation broth, which could also significantly inhibit the pathogenicity of A. alternata. In addition, the UHPLC-Orbitrap Exploris 240 system was employed to analyze the active ingredients in the E-Do8 fermentation broth that inhibit A. alternata, and it was found that E-Do8 only produced surfactin-type compounds, C14-surfactin and surfactin.